2018
DOI: 10.1002/mnfr.201700450
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Grapevine Shoot Extract Containing Resveratrol and Resveratrol Oligomers on Intestinal Adenoma Development in Mice: In Vitro and In Vivo Studies

Abstract: Vineatrol®30 may merit further investigation as a potential dietary gastrointestinal cancer chemopreventive agent in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Resveratrol, a naturally occurring antibiotic plant, has been shown to have potent anti-tumor effect through suppressing proliferation and inducing apoptosis in multiple cancers. 17 , 18 In this study, we also found that resveratrol, as an SIRT1 activator, can also induce protective autophagy which may inhibit the anti-tumor effect of resveratrol via inhibiting Akt/ mTOR and activating p38-MAPK. Therefore, suppressing protective autophagy enhanced anti-tumor effect of resveratrol, making it an effective reagent against NSCLC.…”
Section: Discussionsupporting
confidence: 55%
“…Resveratrol, a naturally occurring antibiotic plant, has been shown to have potent anti-tumor effect through suppressing proliferation and inducing apoptosis in multiple cancers. 17 , 18 In this study, we also found that resveratrol, as an SIRT1 activator, can also induce protective autophagy which may inhibit the anti-tumor effect of resveratrol via inhibiting Akt/ mTOR and activating p38-MAPK. Therefore, suppressing protective autophagy enhanced anti-tumor effect of resveratrol, making it an effective reagent against NSCLC.…”
Section: Discussionsupporting
confidence: 55%
“…Grapevine shoot extracts were tested by Empl et al [ 138 ] in the prevention of human gastrointestinal cancer. Using an ApcMin mice model, which was subject to an HFD like a human model of adenomatous polyposis, the authors observed that grapevine shoot extracts reduce the number (in males) and volume (in females) of intestinal adenoma.…”
Section: Health Benefitsmentioning
confidence: 99%
“…Two experimental pathways have been adopted by Empl et al [ 119 ] to investigate the possibility of using grapevine shoots extracts as agents in the prevention of human gastrointestinal cancer. In vivo research on ApcMin mice, which were subject to a high-fat diet similar to a human model of adenomatous polyposis, reported that both low and high doses of grapevine shoot extracts have the ability to reduce the number (in males) and volume (in females) of intestinal adenoma.…”
Section: Potential Uses Of Grapevine Waste-derived Products In Biomed...mentioning
confidence: 99%